TrustVoucher: automating trust in websites - Dean, Kevin (Kansas State University, 2014)
Since the early 2000s, Internet users have continuously fallen prey to the perils of identity theft and malware . A number of tools have been proposed and implemented to foster trust towards deserving websites and alert users of undeserving websites, including P3P and trust seals. Each of these has fallen short, with studies showing that users simply do not use them. TrustVoucher is a prototype system o forge bonds of trust between users and websites by automatically determining if the website is backed by a trusted third party. Inspiration is taken from the real life way of trusting businesses, in which one aggregates recommendations by friends. TrustVoucher protects users who are attentive to its messages by informing them of sites who have put forth the effort to be endorsed by a trusted third party. An experimental study was performed on the effectiveness of the chosen interface for doing this, and determined that users did not consistently trust the recommendations of TrustVoucher, so future work will explore options for gathering the trust of users to distribute among websites.
Keywords: Trust; Browser; Security; Internet; Computer Science (0984)